PULMONARY ADENOCARCINOMA, A MASQUERADER OF DIFFUSE PARENCHYMAL LUNG DISEASE: A CLINICAL CASE REPORT - Singh B.P.; Pandey Amit Kumar; Singh Apoorva; Palekar Santosh; Patel Mehul Darshak; Kumar Krishan; Gehlot Yogesh; Tiwari Anubha (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Lung cancer  has long intrigued pulmonologists because it seems to have unique epidemiologic, pathologic and clinical features. Lung cancer is one of the most prevalent cancers worldwide. It is typically classified into small-cell lung cancer (SCLC) and the more prevalent non-small-cell lung cancer (NSCLC)1. Lung adenocarcinoma is a subtype of NSCLC that originates mainly in the mucosal glands and accounts for roughly 40% of all lung malignancies and is usually presented with cough, dyspnea, chest pain and weight loss, with some symptom overlap with other lung diseases such as Diffuse parenchymal lung diseases.2 DPLD can present in a range from nodules, ground glassing ,organising pneumonias to diffuse alveolar and interstitial lung involvement, while lung cancers are mostly presented with infiltrative mass, thick-walled cavitations or a solitary nodule with spiculated borders.5 Lung cancer is the most common cancer worldwide. On imaging, it typically presents as mass or nodule. 5Recognition of these typical cases is often straightforward, whereas diagnosis of uncommon manifestations of primary lung cancer is far more challenging. Lung cancer can mimic a variety of benign entities, including pneumonia, lung abscess, postinfectious scarring, atelectasis, a mediastinal mass, emphysema and granulomatous diseases. Lung adenocarcinoma can appear as ground glass nodules, consolidative opacity, or solid mass lesions on computed tomography (CT) 6. It is a glandular tumor with mucin-producing cells that stain positively for mucin on histologyIt would be a misapprehension if the diagnosis is made solely on radiology. Here we present the case of a 54-year-old Indian male,non smoker, who presented with a 2-month history of dry cough and shortness of breath, decreased appatite and weight loss within one month. Chest imaging showed diffuse areas of ground glass attenuation and air space consolidation. The initial impression was that of one with a kind of non-resolving pneumonia with interstitial lung disease ,eosinophilic lung disease ,rarely bronchoalveolar carcinoma as one of the many differentials. Subsequent bronchoscopy with a transbronchial lung cryobiopsy confirmed the diagnosis adenocarcinoma of lung.